PENGEMBANGAN DAN TANTANGAN LEMBAGA PENDIDIKAN ISLAM BERADAPTASI DI ERA TEKNOLOGI DIGITAL - Misda Ariyani; Muhammad Saupiyani; Istiqomah; Suriagiri; M. Nur Effendi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyse the development of madrasahs in the digital age, identify implementation challenges, and formulate self-evaluation-based innovation management as a strategy for adapting to changes in digital technology. The method used is a literature review employing a content analysis approach to books, academic articles, and official documents from 2021 to 2026. The research findings indicate that madrasah development based on EDM and e-RKAM creates an integrated management cycle from quality evaluation to real-time reporting, which promotes professional and transparent governance. Key challenges include limitations in technological infrastructure, low staff competence, resistance to change, funding constraints, regulatory hurdles, data security, the digital divide, a lack of technical support, minimal content integration, and weak monitoring management. Effective innovation management encompasses LMS-based learning, administrative digitisation, interactive learning, strengthening digital literacy and hybrid learning, as well as data-driven decision-making. Self-evaluation via EDM has proven to be a strategic foundation as it measures five quality cultures correlated with the National Education Standards and is integrated with POAC management functions and the PDCA cycle.